Personal, medical and socio-family factors related to the type of coping with stress due to illness in adult oncology patients of a national hospital in Lima - Mamani Quea, Mishell (2021)
Objective: To determine the relationship between coping with stress with the variables sex, age,marital status, educational level, clinical diagnosis, clinical stage, type of treatment and social supportin adult patients of the oncology service of a national hospital in Lima. Methodology: quantitativeapproach, non-experimental design, cross-sectional and correlational type, because it sought to relatethe study variables; The sampling was non-probabilistic consecutive, made up of 100 adult patientsfrom the oncology service from the hospitalization and external consulting areas, with an average ageof 18-80 years; in which, the entire study population was chosen as it met the research requirements.Likewise, the Questionnaire for Coping with Stress in Cancer Patients - CAEPO by González (2004)and the Family and Friends Social Support Scale - AFA-R by Landero and Gonzáles (2008) were usedfor the survey. Results: It was found that between coping with stress and degree of instruction there isa significant association of (X² = 15,274; <. 01); as well as social support (X2 = 22.182 <.000); unlike the other variables where there is no significant association with coping with stress. Conclusion: copingwith stress is significantly related to the degree of education and social support, unlike the variablessex, age, marital status, clinical diagnosis, clinical stage and type of treatment that are not significantly related to coping with stress in patients oncology adults